Why are rare diseases underdiagnosed? A clinical management study on detection of primary biliary cholangitis in primary care - Donato, Francesco; Pigozzi, Marie Graciella; Colarieti, Giulia; Festa, Marco; Tabaglio, Erminio; EPATOMG Working Group (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. There are about 7,000 rare diseases that affect 10% of the world population. Primary biliary cholangitis, an autoimmune chronic liver disease of the interlobular bile ducts, is one of the most common causes of chronic cholestasis. However, it is a rare, often underdiagnosed and undertreated, disease which can lead to cirrhosis and liver failure. We aimed to assess the proportion of undetected primary biliary cholangitis patients in primary care through a clinical management process.Methods. We made two extractions of the clinical data concerning liver diseases, risk factors and laboratory tests from the databases of a sample of general practitioners, with a check and correction of mistakes. The clinical data of the patients without liver disease and major risk factors, and with serum Alkaline Phosphatase above the laboratory reference values, were re-evaluated by each general practitioner with an expert gastroenterologist. The patients with elevated Alkaline Phosphatase values and without evidence of intrahepatic or extrahepatic causes of cholestasis were considered suspected for primary biliary cholangitis and assessed for antimitochondrial antibodies test and specialist’s evaluation, according to present guidelines.Results. A total of 20,480 adults attending 14 general practitioners in the province of Brescia, Northern Italy, were included in the study. Nine patients had a prior primary biliary cholangitis diagnosis, with a prevalence of 43.9/100000. After excluding 2094 (10.2%) patients with liver diseases or other causes of cholestasis, 121 subjects with Alkaline Phosphatase above the reference values were re-evaluated by the general practitioners and gastroenterologist, and 27 patients without symptoms or signs of cholestasis were considered suspected for primary biliary cholangitis: 9 of them were tested for antimitochondrial antibodies, and three new primary biliary cholangitis cases were detected (+33%).Discussion and Conclusions. This study shows that there is a not negligible burden of undetected cases of adult rare diseases that can be diagnosed in primary care, through a disease management procedure, without modifying the routine clinical practice.